Enteral versus parental nutrition after pancreaticoduodenectomy under enhanced recovery after surgery protocol: study protocol for a multicenter, open-label randomized controlled trial (ENE-PAN trial) - Yoshinori Takeda; Yoshihiro Mise; Yoji Kishi; Hiroyuki Sugo; Yusuke Kyoden; Kiyoshi Hasegawa; Yu Takahashi; Akio Saiura (Trials, 2022)
Abstract Background Infectious complications are the main causes of morbidity after pancreaticoduodenectomy (PD). Early enteral nutrition (EN) is a reasonable form of nutritional support that aims to mitigate the occurrence and severity of infectious complications by maintaining gut immunity. However, it remains unclear whether EN is beneficial for patients who underwent PD and are under enhanced recovery after surgery (ERAS) protocol. Methods A multicenter (six hospitals), open-label, randomized controlled trial will be started in July 2022. A total of 320 patients undergoing open PD will be randomly assigned to an EN group or a peripheral parental nutrition (PPN) group in a 1:1 ratio. The stratification factors will be the hospital, age (≥ 70 or not), and preoperative diagnosis (pancreatic cancer or not). In the EN group, enteral nutrition will start on postoperative day (POD) 1 at 200–300 ml/day via the percutaneous tube placed operatively. The volume of the diet will be increased to 400–600 ml/day on POD 2 and depend on the surgeon’s decision from POD 3. In the PPN group, PPN will be delivered after surgery. In both groups, oral feeding will start on POD 3. Each treatment will be finished when patients’ oral food intake reaches 60% of the nutritional requirement (25–30 kcal/day). The primary endpoint will be the occurrence of postoperative infectious complications within 90 days of surgery. The secondary endpoints will be all complications, including major ones such as Clavien–Dindo grade 3 or more and clinically relevant postoperative pancreatic fistula. Data will be analyzed per the intention to treat. Discussion This will be the first, large, and well-designed RCT that aims to determine whether EN is beneficial for patients who underwent PD under the ERAS protocol. According to the results of this study, either EN or PPN would be adopted as the standard nutritional support for patients undergoing PD. Trial registration jRCT1030210691. Registered on March 23, 2022.